2022
DOI: 10.1002/bio.4396
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced photocatalytic activity of ceria‐doped zinc oxide under UV illumination prepared via chemical precipitation

Abstract: Transition metal oxide has emerged as one of the most potential candidates for environment remediation by utilizing solar energy through photocatalysis. This study compares the optical characteristics of zinc oxide (ZnO) and ceria‐doped zinc oxide (CeZnO) nanoparticles synthesized through a facile chemical precipitation method without using any assistant catalyst. The present work investigates the consequences of ceria (cerium dioxide, CeO2) intrusion on the photocatalytic activity of ZnO nanoparticles using m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…The compound was then manually pulverized and calcined at 400 o C for 2 hrs to get the final synthesized. The Ce-doped ZnO nanoparticles were synthesized through the sol-gel method using a mixture of zinc nitrate, Cesium Chloride, urea, ethanol, and DI water [36]. All the analytical grade reagents were received from Merck Pvt.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The compound was then manually pulverized and calcined at 400 o C for 2 hrs to get the final synthesized. The Ce-doped ZnO nanoparticles were synthesized through the sol-gel method using a mixture of zinc nitrate, Cesium Chloride, urea, ethanol, and DI water [36]. All the analytical grade reagents were received from Merck Pvt.…”
Section: Methodsmentioning
confidence: 99%
“…When Ce-ZnO is excited by UV light with a wavelength more than the band gap of the composite, an electron from the valence band jumps to the conduction band leaving behind a hole in the valence band. The CB of CeO2 being higher than that of ZnO, the photogenerated electrons from CeO2 are transferred to the CB of ZnO due to the potential difference between them which in turn enhances the charge transfer mechanism, thereby promoting the photocatalytic activity [36,48].…”
Section: )mentioning
confidence: 99%
“…The results of this study suggested that Cu(2NA‐AMG‐2H 2 O) had outstanding optical properties with a high colouring index, which opened a new avenue for light sources. Kumari et al [56] synthesized ceria‐doped zinc oxide under UV illumination using a chemical precipitation method for photocatalytic degradation of dyes. The obtained results showed that ceria‐doped zinc oxide had good photoactivity related to nano zinc oxide particles for methylene blue dye deterioration by passing UV light.…”
Section: Overview Of Published Researchmentioning
confidence: 99%
“…The single‐step, mass‐scale‐productive, solid‐state reaction method has been adopted for the preparation of Ce‐doped ZnO nanophosphors. To the best of our knowledge, limited literature is available on the synthesis of rare‐earth‐ion (Ce)‐doped ZnO nanophosphors using the solid‐state reaction method and investigated using UV‐sensing properties [27, 30–33, 35, 36]. The present work investigated the efficient PC and enhanced luminescence characteristics from emissive defects in Ce‐doped ZnO nanophosphors for UV sensors, which are not yet reported in any work.…”
Section: Introductionmentioning
confidence: 99%
“…Various dopants such as trivalent transition metals (Sn, Al, Ag, Cu, and Ga) and rare-earth elements (REEs: Dy, Sm, Pr, Eu, La, Gd, Er, and Ce) have been effectively used to control and alter the structural, luminescence and PC characteristics [19][20][21][22][23][24][25][26][27][28][29]. Of these REEs, cerium (Ce) is environment friendly and a very useful dopant for highly luminescent and photoconductor devices [27,[30][31][32]. Easy preparation methods and wide adaptability make ZnO nanophosphors the most promising candidates for various device applications.…”
mentioning
confidence: 99%